Working for Social Justice: A Review of Students as Leaders in Pedagogical Partner Programs - Melissa Scheve; Malia Piper (Social Sciences)
Students as Partners (SaP) programs have centered student voices since their inception. Student–faculty pedagogical partnerships are grounded in the notion that students have the expertise to contribute to faculty in preparing for, reflecting on, and revising teaching and learning practices in ways that are inclusive and responsive to all learners. This expertise is based in part on their lived experiences—both as students and as members of the student populations that SaP programs were intentionally created to help empower (e.g., first generation, low-income, BIPOC (Black, Indigenous, and people of Color) and others marginalized in higher education). These students, in dialogue with faculty, help to expose equity issues across classrooms. As SaP programs have proliferated in colleges and universities across the globe, the student partners’ role as social justice advocates in these programs have expanded too. This review explores the pedagogical partnership literature over the past 20 years, to establish the ways in which undergraduate students and post-bacs have flourished in leadership roles in SaP programs: (a) acting as leaders for social equity on campus, (b) serving as peer mentors to new student partners in existing programs, (c) co-creating new programs, and (d) publishing in the literature. This review reveals opportunities for new directions with peer mentorship in SaP programs through the role of lead student mentors who can help to scale up SaP programs, support the emotional labor involved in partnership work, and create pathways to future social justice leadership opportunities.